A kind of E NF Preparation method of grade lignin-based wood adhesive
Through multi-stage polymerization reaction and formaldehyde capture technology, the problems of long gel time and high formaldehyde release of lignin-based adhesives were solved, and lignin-based wood adhesives that meet ENF grade standards were prepared, which improved the bonding. The strength and reduce formaldehyde emission.
Patent Information
- Application Number
- CN202211287135.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-20
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2042-10-20
AI Technical Summary
The application of existing phenolic resins in indoor environments is limited by the problem of free phenol and formaldehyde release, and lignin-based adhesives have a long gel time, high formaldehyde release and poor glue strength due to complex molecular structure and poor reactivity.
By mixing phenol, water, alkaline solution and lignin with formaldehyde, performing a multi-stage polymerization reaction, and adding formaldehyde trapping agent to adjust the temperature and use of alkaline solution, ENF-grade lignin-based wood adhesive is prepared. Reduce formaldehyde emission and improve bonding strength.
The prepared ENF-grade lignin-based wood adhesive has low free formaldehyde content, short gel time, and high glue strength, which meets the national standards for ENF-grade artificial boards and reduces the formaldehyde emission.
Smart Images

Figure CN115975561B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of wood adhesive preparation, and in particular to an E NF Preparation method of grade lignin-based wood adhesive. Background Art
[0002] Phenolic resin has the advantages of high bonding strength, good weather resistance, water resistance and anti-aging, and is the main glue for outdoor artificial boards. However, phenolic resin has problems such as free phenol and formaldehyde release, which limits its application in indoor environments. Therefore, reducing the free phenol content and formaldehyde release of phenolic resin has become the key to expanding the application of phenolic resin in the artificial board industry.
[0003] As a residue of the biorefining industry, lignin has the advantages of wide sources, renewable and biodegradable. According to statistics, the pulp and paper industry alone produces about 50 million tons of industrial lignin each year worldwide, but most of it is used as low-value fuel or discarded in the natural environment, and has not been fully and effectively utilized and pollutes the environment. A large number of studies have shown that lignin is composed of three basic structural units, has a phenolic resin structure, and contains phenolic hydroxyl groups and rigid benzene rings in the molecule. It is a natural adhesive in plants. Therefore, the use of lignin to prepare E NF However, the complex molecular structure and large steric hindrance of lignin lead to huge differences in the reactivity of different structural units with formaldehyde, resulting in problems such as short gel time, high formaldehyde emission and poor bonding strength of lignin-based adhesives.
[0004] In order to solve the above problems, this application proposes an E NF Preparation method of high-grade lignin-based wood adhesive. Summary of the invention
[0005] (I) Purpose of the invention
[0006] In order to solve the technical problems existing in the background technology, the present invention proposes an E NF The invention discloses a method for preparing a grade lignin-based wood adhesive. Through a simple and green preparation process, the prepared lignin-based wood adhesive has low free formaldehyde content, short gel time, high bonding strength, and formaldehyde release that meets E NF Characteristics of the national standard requirements for grade wood-based panels.
[0007] (II) Technical solution
[0008] In order to solve the above problems, the present invention provides an E NF The preparation method of the grade lignin-based wood adhesive comprises the following steps:
[0009] Step 1, mixing phenol, water, the first batch of alkaline solution, lignin and the first batch of formaldehyde, raising the temperature to a first temperature for reaction, and polymerizing to obtain a first stage reaction product;
[0010] Step 2, adding a second batch of formaldehyde to the first stage reaction product and reacting for 20-30 minutes to obtain an intermediate reactant, then adding a second batch of alkaline solution, adjusting the system temperature to a second temperature, and performing a polymerization reaction to obtain a second stage reaction product;
[0011] Step 3: Add the third batch of formaldehyde to the second stage reaction product and react for 15-25 minutes, add the third batch of alkaline solution, wait for polymerization to the target viscosity, add formaldehyde scavenger, cool to 40-45°C to obtain E NF Grade lignin-based wood adhesive.
[0012] Preferably, in step 1, the weight portions of the phenol, the first batch of alkaline solution, the lignin and the first batch of formaldehyde are 100 parts, 75-100 parts, 100-150 parts and 80-150 parts respectively.
[0013] Preferably, in step 1, the first temperature is 80-98°C.
[0014] Preferably, in step 2, the weight portions of the second batch of alkaline solution and the second batch of formaldehyde are 50-75 parts and 80-150 parts respectively.
[0015] Preferably, in the step 2, the second temperature is 80-98°C.
[0016] Preferably, in step three, the weight portions of the third batch of alkaline solution, the third batch of formaldehyde and the formaldehyde trapping agent are 75-100 parts, 40-75 parts and 15-30 parts respectively.
[0017] Preferably, in step three, the target viscosity is 45-4000 mPa·s.
[0018] Preferably, the first batch of alkaline solution, the second batch of alkaline solution and the third batch of alkaline solution are at least one of sodium hydroxide solution, potassium hydroxide solution and calcium oxide solution.
[0019] Preferably, the formaldehyde trapping agent is urea.
[0020] Preferably, the polymerization reaction time of the phenol, water, the first batch of alkaline solution, lignin and the first batch of formaldehyde at the first temperature in the step 1 is 55-65 minutes;
[0021] The polymerization reaction time of the intermediate reactant and the second batch of alkaline solution at the second temperature in the step 2 is 55-65 minutes.
[0022] The above technical solution of the present invention has the following beneficial technical effects:
[0023] 1. An E provided by the present invention NF The preparation method of the grade lignin-based wood adhesive comprises the following steps: reacting lignin with formaldehyde and curing the lignin with formaldehyde to prepare the grade E NF Grade lignin-based wood adhesive;
[0024] 2. The present invention provides an E NF The invention discloses a method for preparing a high-grade lignin-based wood adhesive, which uses phenol as an active auxiliary agent, can promote the rapid curing of the lignin-based wood adhesive, improve the bonding strength of the resin, and reduce the formaldehyde emission of the resin. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 It is the structural characterization of the reaction product of the model compound of the guaiac-type lignin structural unit and formaldehyde;
[0026] Figure 2 The relationship between the model compound of guaiac-type lignin structural unit and formaldehyde over time;
[0027] Figure 3 It is the structural characterization of the reaction product of the model compound of the p-hydroxyphenyl type lignin structural unit and formaldehyde;
[0028] Figure 4 This is a graph showing the relationship between the p-hydroxyphenyl lignin structural unit model compound and formaldehyde over time;
[0029] Figure 5 This is a representation diagram of the lignin structure. DETAILED DESCRIPTION
[0030] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.
[0031] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0032] Example 1
[0033] In the first step, 100 g of phenol and water were added to the reactor, and then stirring was started, 80 g of sodium hydroxide solution, 125 g of lignin and 90 g of formaldehyde were added, and the temperature was raised to 90° C. The first stage of polymerization reaction was 60 min;
[0034] The second step is to add 90g of formaldehyde and react for 20-30min, then add 50g of sodium hydroxide solution and control the system temperature at 90°C for 60min;
[0035] The third step is to add 45g of formaldehyde and react for 20min, then add 75g of sodium hydroxide solution, wait for polymerization until the viscosity reaches 405mPa·s, add 15g of urea, and cool to 40-45℃ to obtain E NF Grade lignin-based wood adhesive, denoted as LWA1 resin.
[0036] The viscosity, gel time, free formaldehyde content and formaldehyde release of the obtained LWA1 resin are shown in Table 1. The resin viscosity is 405mPa·s, which is higher than the comparative PF resin by 178mPa·s, but significantly lower than the comparative PVAc resin by 2458mPa·s. This is because LWA1 and PF resin are prepolymers prepared by gradual polycondensation, which can ensure good rheological behavior in the plywood gluing process, while PVAc resin is a high molecular polymer formed by free radical polymerization of vinyl monomer vinyl acetate, resulting in its high viscosity. The free formaldehyde content of LWA1 resin is only 0.05%, which is significantly lower than that of the comparative PF resin, indicating that lignin and formaldehyde have fully reacted. The gel time of LWA1 resin is 28min±2min, the same as that of the comparative PF resin, indicating that the problem of low lignin reaction activity has been improved. In terms of bonding strength, the comparative PF resin (1.06MPa) and LWA1 resin (1.27MPa) both meet the requirements of boiling water resistance bonding strength of Class I plywood in GB / T17657-2013, which is significantly higher than that of the comparative PVAc. However, the formaldehyde emission of LWA1 resin was not detected by the dryer method, which meets the requirements of E NF Grade plywood requirements.
[0037] Example 2
[0038] In the first step, 100 g of phenol and water were added to the reactor, and then stirring was started. 100 g of a mixture of potassium hydroxide and calcium oxide in a mass ratio of 80:20, 100 g of lignin and 80 g of formaldehyde were added, and the temperature was raised to 80° C. The first stage of polymerization reaction was carried out for 60 min.
[0039] In the second step, 80 g of formaldehyde was added and reacted for 20-30 min, then 50 g of a mixture of potassium hydroxide and calcium oxide in a mass ratio of 80:20 was added, and the system temperature was controlled at 80° C. for polymerization for 60 min;
[0040] In the third step, 40g of formaldehyde was added to react for 20min, and a mixture of 75g of potassium hydroxide and calcium oxide with a mass ratio of 80:20 was added. After polymerization to a viscosity of 45mPa·s, 30g of urea was added and the temperature was lowered to 40-45°C to obtain E NFGrade lignin-based wood adhesive, recorded as LWA2 resin.
[0041] The viscosity, gel time, free formaldehyde content and formaldehyde release of the obtained LWA2 resin are shown in Table 1. The resin viscosity is 45mPa·s, which is significantly lower than the viscosity of LWA1 and the comparative PF resin. This indicates that when the polymerization temperature is low and the amount of formaldehyde is low, the degree of reaction between lignin and formaldehyde is slightly lower, resulting in a lower degree of resin prepolymerization, which in turn causes the gel time to be extended to 40min±3min. The free formaldehyde content in the LWA2 resin increased to 0.12%, which also proves that the low polymerization temperature leads to a low degree of reaction between lignin and formaldehyde during the polymerization process. However, the bonding strength of the LWA2 resin prepared at a low polymerization temperature and a low amount of formaldehyde can still reach 0.80MPa, and the formaldehyde release is as low as 0.014mg / L, which meets the requirements of E NF Grade plywood requirements.
[0042] Example 3
[0043] In the first step, 100 g of phenol and water were added to the reactor, and then stirring was started, 75 g of a solution of potassium hydroxide and sodium hydroxide in a mass ratio of 50:50, 150 g of lignin and 150 g of formaldehyde were added, and the temperature was raised to 95° C. The first stage of polymerization reaction was carried out for 60 min;
[0044] The second step is to add 150g of formaldehyde and react for 20-30min, then add 75g of a solution of potassium hydroxide and sodium hydroxide in a mass ratio of 50:50, and control the system temperature to 95°C for polymerization for 60min;
[0045] In the third step, add 75g of formaldehyde and react for 20min, add 75g of a solution of potassium hydroxide and sodium hydroxide in a mass ratio of 50:50, add 15g of urea, and cool to 40-45°C to obtain E NF Grade lignin-based wood adhesive, recorded as LWA3 resin.
[0046] The viscosity, gel time, free formaldehyde content and formaldehyde release of the obtained LWA3 resin are shown in Table 1. The resin viscosity is 1158 mPa·s, which is higher than the viscosity of LWA1 and the comparative PF resin, but lower than the comparative PVAc resin. This is because the preparation method of increasing the polymerization temperature and the amount of formaldehyde promoted the reaction between lignin and formaldehyde, resulting in an increase in the degree of resin prepolymerization, thereby shortening the gel time of the resin to 24 min±2 min. The formaldehyde content of the LWA3 resin is as high as 375 g, which is the highest amount in all embodiments, but the polymerization temperature of 95°C increases the reaction activity of formaldehyde with lignin and phenol, so the free formaldehyde content of the LWA3 resin is only 0.05%, which is the same as LWA1 and significantly lower than LWA2 and the comparative PF resin. The bonding strength of the LWA3 resin reaches 1.22 MPa, and the formaldehyde release is 0.035 mg / L, which further illustrates that the present invention can be used to produce E NF Grade I plywood products.
[0047] Example 4
[0048] In the first step, 100 g of phenol and water were added to the reactor, and then stirring was started. 100 g of a mixture of sodium hydroxide and calcium oxide in a mass ratio of 90:10, 120 g of lignin and 100 g of formaldehyde were added, and the temperature was raised to 95° C. The first stage of polymerization reaction was carried out for 60 min.
[0049] In the second step, 100 g of formaldehyde was added and reacted for 20-30 min, then 80 g of a mixture of sodium hydroxide and calcium oxide in a mass ratio of 90:10 was added, and the system temperature was controlled at 88° C. for polymerization for 60 min;
[0050] In the third step, 60 g of formaldehyde was added to react for 20 min, 80 g of a mixture of sodium hydroxide and calcium oxide with a mass ratio of 90:10 was added, 20 g of urea was added, the reaction temperature reached 326 mPa·s, and the temperature was lowered to 40-45°C to obtain E NF Grade lignin-based wood adhesive, recorded as LWA4 resin.
[0051] The viscosity, gel time, free formaldehyde content and formaldehyde release of the obtained LWA4 resin are shown in Table 1. The resin viscosity is 386 mPa·s, which is higher than the viscosity of LWA2 and the comparative PF resin, equivalent to LWA1, but lower than the comparative PVAc resin, indicating that the LWA resin also has good rheological behavior in application. The gel time of LWA4 resin is 27 min ± 2 min, the bonding strength reaches 1.13 MPa, and no formaldehyde release is detected by the dryer method, which further indicates that the present invention can be used to produce E NF Grade I plywood products.
[0052] Example 5
[0053] In the first step, 100 g of phenol and water were added to the reactor, and then stirring was started, 100 g of sodium hydroxide aqueous solution, 130 g of lignin and 140 g of formaldehyde were added, and the temperature was raised to 90° C. The first stage of polymerization reaction was carried out for 60 min;
[0054] In the second step, 140 g of formaldehyde was added and reacted for 20-30 min, then 75 g of sodium hydroxide aqueous solution was added and the system temperature was controlled at 90° C. for polymerization for 60 min;
[0055] In the third step, add 70g of formaldehyde and react for 20min, add 100g of sodium hydroxide aqueous solution, add 30g of urea, react to 575mPa·s, cool to 40-45℃, and obtain E NF Grade lignin-based wood adhesive, recorded as LWA5 resin.
[0056] The viscosity, gel time, free formaldehyde content and formaldehyde release of the obtained LWA5 resin are shown in Table 1. The resin viscosity is 575 mPa·s, which is higher than the viscosity of LWA1, LWA2, LWA4 and the comparative PF resin, but lower than the comparative PVAc resin, indicating that the LWA resin also has good rheological behavior in application. The gel time of LWA5 resin is 28 min ± 2 min, the bonding strength reaches 1.17 MPa, and no formaldehyde release is detected by the dryer method, which further indicates that the present invention can be used to produce E NF Grade I plywood products.
[0057] Comparative Example 1
[0058] Phenolic resin is formed by the gradual polycondensation of phenol and formaldehyde under the action of alkaline solution. It has the advantages of high bonding strength, good weather resistance, water resistance and anti-aging, and is the main glue for Class I plywood. Here, a common phenolic resin on the market, namely PF resin, is selected as Comparative Example 1.
[0059] Comparative Example 2
[0060] Polyvinyl acetate emulsion is widely used in the production of E NF Here, a common polyvinyl acetate emulsion, PVAc resin, is selected as comparative example 2.
[0061] Test Method Description
[0062] Resin viscosity test: The rotational viscosity of the resin measured by a rotational viscometer in an environment of 25°C ± 2°C is the viscosity described in the present invention.
[0063] Gel time: Take 5g of resin in a test tube and immerse it in 100℃ boiling water. The time it takes for the resin to condense into a mass is the gel time.
[0064] According to GB / T 17657-2013 "Test methods for physical and chemical properties of wood-based panels and veneer wood-based panels" Class I board requirements, the boiling water resistance bonding strength of eucalyptus five-layer plywood is tested as follows: 2 The plywood test specimens were immersed in 100℃ boiling water for 4 hours, taken out and dried at 60℃ for 16-20 hours, immersed in 100℃ boiling water for 4 hours again, and then cooled in cold water. The tensile shear strength of the specimens was tested by a universal mechanical testing machine, which is the bonding strength of the resin.
[0065] The free formaldehyde content was determined according to GB T 14074-2006, which is briefly described as follows: 2.0 g of resin was dissolved in 50 ml of distilled water, the pH value was adjusted to 3.5, 10 ml of hydroxylamine hydrochloride solution (mass fraction was 10%) was added, and the reaction was carried out at room temperature for 10 min. 0.1 mol / L sodium hydroxide standard solution was used to titrate to pH 3.5, a blank was set, and the free formaldehyde content of the resin was calculated by the sodium hydroxide consumption.
[0066] The formaldehyde emission dryer method is briefly described as follows: 10 pieces of 150×75mm 2 The sample was placed in a desiccator containing 300 mL of deionized water and stored at 20°C for 24 hours. The formaldehyde emission of the plywood was detected by color development using ammonium acetate and acetylacetone solution method, and a UV-visible spectrophotometer was used at 412 nm. The test was performed three times in parallel and the average value was calculated.
[0067] According to GB / T 39600-2021 "Classification of formaldehyde emission of wood-based panels and their products" 3 The formaldehyde emission of plywood measured by the climate chamber method is 0.012 mg / m 3 , further indicating that a hot pressing time of 120s / mm is sufficient to realize the application of LWA2 in the production of ENF grade I plywood.
[0068] Table 1 E obtained in different embodiments NF Viscosity, gel time, free formaldehyde content, bonding strength and formaldehyde emission of grade lignin-based wood adhesives
[0069]
[0070] 1. Experiment on the selection of lignin types: specifically, the reaction activity experiment of guaiac-type (G type) and p-hydroxyphenyl-type (H type) lignin structural units with formaldehyde:
[0071] 1.1 Experimental Materials
[0072] 4-Ethylphenol (LMH, H-type lignin structural unit model compound), 2-methoxy-4-propylphenol (LMG, G-type lignin structural unit model compound) (analytical grade), Shanghai MacLean Biochemical Technology Co., Ltd.; 2-Chloro-4,4,5,5-tetramethyl-1,3,2-dioxaphospholane (TMDP), N-hydroxy-5-norbornene-2,3-dicarboxylic acid (HONB), chromium acetylacetonate, analytical grade, Aladdin Chemical Reagent Co., Ltd.; 37% formaldehyde solution (F), urea (U), phenol (P), sodium hydroxide, ethyl acetate are all analytical grade, Nanjing Chemical Reagent Co., Ltd.; methanol (chromatographic grade), TEDIA, USA; distilled water, Wahaha Group Co., Ltd.; lignin, industrial grade, Shandong Longli Biotechnology Co., Ltd.; commercial phenolic resin, industrial product, provided by Zhonglin Adhesive Technology Co., Ltd.;
[0073] 1.2 Hydroxylation reaction of lignin model compounds
[0074] Take 10 mmol LMH and LMG respectively, add 20 mmol formaldehyde solution to each in a 5 mL reaction bottle to adjust the pH value to 8.5-9.5, and heat to 80°C under magnetic stirring for reaction. Samples are taken at different times, and the hydroxymethylation reaction rate is measured by high performance liquid chromatography (HPLC).
[0075] 1.3 Synthesis of lignin phenolic resin
[0076] Add 2.0 kg of phenol, 2.5 kg of water and 1.5 kg of sodium hydroxide solution (mass fraction of 30%) into a 20 L reactor, start stirring, add 2.5 kg of lignin and a set amount of formaldehyde, heat to the set temperature and react for 1 hour; cool to 80°C, add a second batch of set amount of formaldehyde solution and 1.0 kg of the above sodium hydroxide solution, heat to the set temperature and react for 60 minutes; add a third batch of set amount of formaldehyde solution, heat to the set temperature and react for 60 minutes; add 0.6 kg of urea, cool to below 40°C, discharge, and obtain lignin phenolic resin.
[0077] 1.4 Physical and chemical properties test of lignin phenolic resin
[0078] Resin viscosity, gel time (100°C), free formaldehyde content and free phenol content were determined according to GB / T 14074-2006.
[0079] 1.5 Preparation of five-layer eucalyptus plywood
[0080] Veneer: Eucalyptus veneer size 400mm×400mm×2mm, moisture content 8-12%; Glue adjustment process: Add 5-20% of the resin mass of flour to the lignin phenolic resin and stir evenly; Double-sided glue application amount: 280-300g / m 2; Pre-press at 1.0MPa for 1h at room temperature, and hot press at 120℃ and 1.0MPa.
[0081] 1.6 Performance test of plywood
[0082] The boiling water resistance bonding strength test method of eucalyptus five-layer plywood is as follows: overlap the area of 25×25cm 2 The plywood test specimens are immersed in 100℃ boiling water for 4 hours, taken out and dried at 60℃ for 16-20 hours, immersed in 100℃ boiling water again for 4 hours, and then cooled in cold water. The tensile shear strength of the specimens is tested by a universal mechanical testing machine, which is the boiling water resistance bonding strength of the plywood.
[0083] The formaldehyde emission dryer method is briefly described as follows: 10 pieces of 150×75mm 2 The sample was placed in a desiccator containing 300 mL of deionized water and stored at 20°C for 24 hours. The formaldehyde emission of the plywood was detected by color development using ammonium acetate and acetylacetone solution method, and a UV-visible spectrophotometer was used at 412 nm. The test was performed three times in parallel and the average value was calculated.
[0084] 1.7 Characterization
[0085] Infrared spectroscopy (FT-IR): A Nicolet iS10 infrared spectrometer was used at 4 cm -1 Resolution 4000-600cm -1 16 scans were performed over a wavenumber range of 1.33 nm and the FT-IR spectra were recorded.
[0086] H NMR ( 1 H NMR), carbon spectrum ( 13 C NMR: Deuterated dimethyl sulfoxide was used as the deuterated reagent, and the measurements were performed on a Bruker AVANCE3 400 MHz NMR spectrometer at 400 and 101 MHz scanning frequencies. 1 H NMR and 13 C NMR spectrum.
[0087] Phosphorus NMR spectroscopy ( 31 P NMR): Pyridine-deuterated chloroform with a volume ratio of 1.6:1 was used as the solvent, N-hydroxy-5-norbornene-2,3-dicarboxylic acid (HONB) was used as the internal standard, and trivalent chromium acetylacetonate was used as the relaxation reagent. After thorough mixing, the phosphating reagent TMDP was added for phosphating treatment. After 15 minutes, the sample signal was collected using a Bruker AVANCE3 600 MHz NMR instrument.
[0088] HPLC analysis: Using 20:80 water-methanol as the mobile phase at a flow rate of 1.0 ml / min, the hydroxymethyl conversion rate of different model compounds of lignin was quantitatively determined by a C18 Gemini 5μm 250×4.6mm LC-MS analytical column; each reaction product was separated and purified by an EclipseXDB-C18 5μm 250×9.4mm semi-preparative column.
[0089] 2. Results and Discussion
[0090] 2.1 Effect of lignin structural unit types on hydroxymethylation activity
[0091] Figure 1 LMG before and after hydroxymethylation 1 H NMR and 13 C NMR spectrum. Analysis of LMG 1 H NMR spectrum, the dd peaks (ortho-meta hydrogen coupling splitting), d peak (ortho hydrogen coupling splitting) and d peak (meta hydrogen coupling splitting) at δH 6.54, 6.69 and 6.72 were attributed to the d, e and f hydrogen atoms of the LMG benzene ring, respectively; the hydroxymethylated derivative (HLMG) 1 The H NMR spectrum showed broad single peaks of 2H and 1H at δH 4.49 and 4.93, respectively, which were attributed to the hydrogen atoms of the hydroxymethyl group (Ph-CH2OH), and the d peaks at δH 6.66 and 6.75 corresponded to the two hydrogen atoms at the meta position of the phenolic hydroxyl group. 13 The Ph-CH2-carbon signal appeared at δC 58.7 in C NMR, and the ortho-carbon signal of the unsubstituted phenolic hydroxyl group at δC 115.2 disappeared, indicating that the G-type lignin structural unit can react with formaldehyde to form hydroxymethyl.
[0092] Figure 2 For LMH and its hydroxymethylated derivatives 1 H NMR and 13 C NMR spectrum. Figure 2 The chemical shifts of hydrogen atoms in A are assigned as follows: LMH benzene ring hydrogen atoms: δ H 6.69, dd peak; δ H 6.99, dd peak; monohydroxymethyl derivative (1HLMH) benzene ring hydrogen atom: δ H 6.66, d peak; δ H 6.86, dd peak; δ H 7.11, d peak; hydroxymethyl hydrogen atom (Ph-C H2 OH):δ H 4.45, s peak; δ H 4.91, br peak (hydroxyl hydrogen atom Ph-CH2O H ); dihydroxymethyl derivative (2HLMH) benzene ring hydrogen atom: δH 6.98, s peak; hydroxymethyl hydrogen atom (Ph-C H2 OH):δ H 4.53, br peak. Analysis Figure 2 B's 13 C NMR, 1HLMH and 2HLMH hydroxymethyl carbon (Ph- C H2OH) signals appear at δ C 58.8 and δ C 59.9. It can be seen that the H-type lignin structural unit can react with formaldehyde to produce monomethylol and dimethylol derivatives.
[0093] In order to study the effect of methoxyl group (-OCH3) on the hydroxymethylation activity of lignin, the hydroxymethylation reaction rates of LMG and LMH were analyzed by HPLC peak area normalization method. Figure 3 and Figure 4 As shown. Figure 3 From A and B, we can see that the LMG hydroxymethylation reaction process can be divided into three stages. In the first stage (0-90min), the hydroxymethylation reaction rate is constant at 0.55% / min; in the second stage, the reaction rate gradually decreases (90-240min), and finally reaches a dynamic equilibrium, with an equilibrium conversion rate of only 79.6%. Figure 4 It was found that LMH can undergo hydroxymethylation reaction quickly to generate a monohydroxymethyl derivative (1HLMH); further, a dihydroxymethyl derivative (2HLMH) can be generated quickly, and the yield of 2HLMH can reach 99% after 45 minutes, indicating that -OCH3 has a significant effect on the reaction activity of the hydroxymethyl group of the lignin structural unit.
[0094] 2.2 Analysis of lignin characteristics
[0095] Based on the above research results, in order to determine the hydroxymethylation activity of lignin, FT-IR spectroscopy and 31 PNMR spectrum ( Figure 5 ) studied the molecular structure characteristics of lignin. Observe the FT-IR spectrum of lignin ( Figure 5 A) It can be seen that 3340cm -1 The characteristic absorption peaks of hydroxyl groups are at 2925 and 2838 cm -1 The characteristic absorption peaks of -CH are at 1600 and 1500 cm -1 The absorption peak is the characteristic absorption peak of lignin benzene ring. Figure 5 B is phosphated lignin 31 P NMR spectrum, H-type, G-type and syringyl (S-type) phenolic hydroxyl derivative signals appear at δ P137.2-138.6, 138.7-140.3 and 140.4-145.0. Using HONB as internal standard, the contents of H-type, G-type and S-type were 0.07mmol / g, 1.64mmol / g and 1.75mmol / g, respectively. It can be seen that the phenolic hydroxyl groups in lignin mainly come from G-type and S-type structural units, and the H-type phenolic hydroxyl groups only account for about 2% of the total phenolic hydroxyl content. Therefore, the reaction activity of lignin with formaldehyde is low.
[0096] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited by the above embodiments. The above embodiments and descriptions are only preferred examples of the present invention and are not intended to limit the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A kind of E NF The method for preparing a grade lignin-based wood adhesive is characterized in that: The following steps are involved: In the first step, 100 g of phenol and water were added to the reactor, and then stirring was started, 80 g of sodium hydroxide solution, 125 g of lignin and 90 g of formaldehyde were added, and the temperature was raised to 90 °C. The first stage of polymerization reaction was 60 min. The second step is to add 90g of formaldehyde and react for 20-30 minutes, then add 50g of sodium hydroxide solution and control the system temperature at 90°C for polymerization for 60 minutes; The third step is to add 45g of formaldehyde and react for 20 min, then add 75g of sodium hydroxide solution, wait until the viscosity is 405 mPa·s, add 15g of urea, and cool to 40-45°C to obtain E NF Grade lignin-based wood adhesive.
2. A method for preparing an ENF-grade lignin-based wood adhesive, characterized in that: The following steps are involved: In the first step, 100 g of phenol and water were added to the reactor, and then stirring was started. 100 g of a mixture of sodium hydroxide and calcium oxide with a mass ratio of 90:10, 120 g of lignin and 100 g of formaldehyde were added, and the temperature was raised to 95 °C. The first stage of polymerization reaction was carried out for 60 min. In the second step, 100 g of formaldehyde was added and reacted for 20-30 min, then 80 g of a mixture of sodium hydroxide and calcium oxide in a mass ratio of 90:10 was added, and the system temperature was controlled at 88 °C for polymerization for 60 min; In the third step, 60 g of formaldehyde was added to react for 20 min, 80 g of a mixture of sodium hydroxide and calcium oxide with a mass ratio of 90:10 was added, 20 g of urea was added, the reaction temperature reached 326 mPa·s, and the temperature was lowered to 40-45 °C to obtain E NF Grade lignin-based wood adhesive.
3. A method for preparing an ENF-grade lignin-based wood adhesive, characterized in that: The following steps are involved: In the first step, 100 g of phenol and water were added to the reactor, and then stirring was started. 100 g of sodium hydroxide aqueous solution, 130 g of lignin and 140 g of formaldehyde were added, and the temperature was raised to 90 °C. The first stage of polymerization reaction was carried out for 60 min. In the second step, 140 g of formaldehyde was added and reacted for 20-30 min, then 75 g of sodium hydroxide aqueous solution was added and the system temperature was controlled at 90° C. for 60 min. In the third step, 70 g of formaldehyde was added and reacted for 20 min, 100 g of sodium hydroxide aqueous solution was added, 30 g of urea was added, the reaction temperature reached 575 mPa·s, and the temperature was lowered to 40-45 °C to obtain E NF Grade lignin-based wood adhesive.
Citation Information
Patent Citations
Method of preparing alkali lignin modified phenolic resin
CN101492522A
Preparation method of biomass-based phenolic resin wood adhesive
CN102634308A
Method for preparing lignin-based environment-friendly phenolic resin adhesive
CN103804618A
Preparation method of green phenolic resin adhesive with high lignin substituted ratio
CN108587538A
Lignhin resin adhesive
JP1988112677A
